If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(x + -3) + 2x = -3 Reorder the terms: 5 + -1(-3 + x) + 2x = -3 5 + (-3 * -1 + x * -1) + 2x = -3 5 + (3 + -1x) + 2x = -3 Combine like terms: 5 + 3 = 8 8 + -1x + 2x = -3 Combine like terms: -1x + 2x = 1x 8 + 1x = -3 Solving 8 + 1x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 1x = -3 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = -3 + -8 1x = -3 + -8 Combine like terms: -3 + -8 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| 8=2(3x-1)+2(4x+5) | | 13.8(w+5)=44 | | 46x+4=2x+36 | | 2x(-3x^2+22x-7)=0 | | 5-3(2-x)=-4 | | 2x^2=8-3x | | x/-15=18 | | N^2+N-332=0 | | 2Inx=2 | | 5x+3-9x=12-14x+10x-9 | | 2-3(x+5)=5x-21 | | 5x+3-9x=12 | | 12[20-2(6^2/3•2^2)] | | -4p+19=-11 | | y=-0.6+0.2r | | -19+x=x+10 | | .44=log(x) | | 2(3x+5)+5(2x-1)=1 | | (2+3)y-9=r-12 | | x-3=-3x-6 | | 5x-8=81 | | 3x+1-2x=9-3 | | .75x-2x=7 | | 169x^2-81y^2=0 | | 8y-3(3-2y)=5 | | d=1/2(at2) | | 1/6(6x-1)=-2/7-4/7 | | X^2+10+2=0 | | 2k+k=125 | | 4x+2+(4-x)= | | 3/5p-5 | | 3/4y-2/3x=12 |